Formal Requirements for the Revision of the TNI Law from the Perspective of Public Participation - Setiawan, Risman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The process of formulating legislation in Indonesia requires the fulfillment of formal requirements, one of which is public participation. Public participation is a crucial pillar in ensuring democratic legitimacy and the quality of the substance of laws. However, the 2025 revision of Law Number 34 of 2004 concerning the Indonesian National Armed Forces is considered to ignore this principle. The closed-door discussions, minimal socialization, and the absence of involvement of civil society, academics, and other stakeholders have given rise to criticism of the integrity of the legislative process. This study aims to analyze the formal requirements for the revision of the TNI Law from the perspective of Public Participation as stipulated in Law Number 12 of 2011 and the Constitutional Court Decision. The TNI Law revision process does not fully implement the principle of participation, thus potentially creating formal flaws that can become the basis for formal testing (judicial review), weaken legal legitimacy and threaten the principle of popular sovereignty in a democratic state. Therefore, this study emphasizes the need to strengthen legislative oversight mechanisms and institutionalize public participation as an absolute requirement in the process of formulating laws in Indonesia.